Navigating stress: Parenting styles and coping patterns in Bandung’s Generation Z igating Stress: Parenting Styles and Coping Patterns in Bandung’s Generation Z - Ilmi Hakim (UIN Maulana Malik Ibrahim Malang, 2026)
Generation Z has grown up in a digital era marked by high creativity, broad social connectivity, and intensive engagement with technology. However, these developments are accompanied by increased vulnerability to stress and anxiety. This study examined the relationship between perceived parenting styles and coping strategies among Generation Z. A quantitative correlational design was employed, with participants selected using accidental sampling from Generation Z individuals residing in Bandung who met the study's inclusion criteria. The Scale of Perceived Parenting Styles (SOPPS) was used to measure parenting styles, while the Ways of Coping Scale (WOCS) assessed coping strategies. Data were analyzed using Pearson’s correlation after the assumptions of normality and linearity were satisfied. The findings indicated that only several dimensions of perceived parenting styles were significantly associated with coping strategies, whereas other relationships were not statistically significant. Significant associations were observed in both positive and negative directions, suggesting that the relationship between parenting styles and coping is more nuanced than a uniformly positive pattern. Overall, participants who perceived more supportive parenting tended to report greater use of adaptive coping strategies, whereas less supportive parenting was associated with a greater tendency toward avoidance-oriented coping in specific parenting dimensions. These findings highlight that the association between parenting styles and coping strategies varies across parenting dimensions and should be interpreted within broader developmental and sociocultural contexts. The study provides evidence that may inform the development of interventions and counseling services to support the psychological well-being of adolescents and young adults in the digital age KEY WORDS: Generation Z; parenting styles; coping strategies; emotional regulation; psychological resilience Copyright ©2026. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0